In Vitro Antiplasmodial, Heme Polymerization, and Cytotoxicity of Hydroxyxanthone Derivatives - Mistika Zakiah; Rul Afiyah Syarif; Mustofa Mustofa; Jumina Jumina; Nela Fatmasari; Eti Nurwening Sholikhah (Journal of Tropical Medicine)
The previous study showed that xanthone had antiplasmodial activity. Xanthone, with additional hydroxyl groups, was synthesized to increase its antiplasmodial activity. One of the strategies to evaluate a compound that can be developed into an antimalarial drug is by testing its mechanism in inhibiting heme polymerization. In acidic condition, hematin can be polymerized to β-hematin in vitro, which is analog with hemozoin in Plasmodium. This study was conducted to evaluate the antiplasmodial activity of hydroxyxanthone derivative compounds on two strains of Plasmodium falciparum 3D-7 and FCR-3, to assess inhibition of heme polymerization activity and determine the selectivity of hydroxyxanthone derivative compounds. The antiplasmodial activity of each compound was tested on Plasmodium falciparum 3D-7 and FCR-3 with 72 hours incubation period, triplicated in three replications with the microscopic method. The compound that showed the best antiplasmodial activity underwent flow cytometry assay. Heme polymerization inhibition test was performed using the in vitro heme polymerization inhibition activity (HPIA) assay. The antiplasmodial activity and heme polymerization inhibition activity were expressed as the 50% inhibitory concentration (IC50). In vitro cytotoxicity was tested using the MTT assay method on Vero cell lines to determine its selectivity index. The results showed that among 5-hydroxyxanthone derivative compounds, the 1,6,8-trihydroxyxanthone had the best in vitro antiplasmodial activity on both 3D-7 and FCR-3 Plasmodium falciparum strains with IC50 values of 6.10 ± 2.01 and 6.76 ± 2.38 μM, respectively. The 1,6,8-trihydroxyxanthone showed inhibition activity of heme polymerization with IC50 value of 2.854 mM and showed the high selectivity with selectivity index of 502.2–556.54. In conclusion, among 5-hydroxyxanthone derivatives tested, the 1,6,8-trihydroxyxantone showed the best antiplasmodial activity and has heme polymerization inhibition activity and high selectivity.